Impact of Job Satisfaction, Transformational Leadership, and Work-Life Balance on Employee Performance: A Study in Technology Companies in Indonesia - Marnoto, Marnoto; Supardi, Supardi; Soegiarto, Ita (IJBLE Scientific Publications Community Inc., 2024)
This research explores the dynamic interplay of job satisfaction, transformational leadership, work-life balance, and their collective impact on employee performance within the burgeoning technology sector of Indonesia. The study employs a quantitative research design, utilizing Partial Least Squares Structural Equation Modeling (PLS SEM) to analyze data gathered through a questionnaire survey of employees in various technology companies. The findings reveal a robust and positive association between job satisfaction and employee performance, emphasizing the need for organizations to prioritize initiatives that cultivate positive work environments. While the study did not establish a direct link between transformational leadership and employee performance within the specific model, it underscores the nuanced dynamics of leadership impact. Additionally, the research highlights the highly significant and positive relationship between work-life balance and employee performance, emphasizing the crucial role of promoting a healthy balance between work and personal life in enhancing overall employee effectiveness.